Rapid Local Expression of Interleukin-12, Tumor Necrosis Factor Alpha, and Gamma Interferon after Cutaneous Francisella tularensis Infection in Tularemia-Immune Mice - Stenmark, Stephan (American Society for Microbiology, 1999)
Francisella tularensis LVS is an effective live vaccine strain used for cutaneous vaccination against tularemia in man. In mice, injection of LVS causes invasive disease and subsequent development of immunity that is characterized by effective control of otherwise lethal doses of the organism. In the present investigation, it is shown that LVS-immune mice controlled an intradermal infection much more effectively than did naive mice; bacterial counts in skin samples were 1.5 to 2.0 log(10) lower 24 h after injection and 6 log(10) lower 72 h after injection in immune mice. Moreover, in contrast to naive mice, no bacteria were demonstrated in samples from livers and spleens of immune mice. By immunohistochemistry, skin samples from immune mice showed an intense staining for interleukin-12 (IL-12) and a moderate staining for tumor necrosis factor alpha (TNF-α) at 24 h postinoculation, after which staining for both cytokines faded. In naive mice, the staining for IL-12 was weak at all time points and no staining for TNF-α was observed. No staining for gamma interferon (IFN-γ) was observed in any group before 72 h. At that time point, skin samples from immune mice showed moderate staining and skin samples from naive mice showed weak staining. Reverse transcriptase PCR showed an induction of mRNA of the three cytokines in the skin within the first day after injection. A quantitative analysis demonstrated higher IFN-γ and TNF-α mRNA levels in immune mice at 24 h postinoculation. In conclusion, immunization with F. tularensis LVS conferred a capability to respond to cutaneous reinfection, with rapid local expression of IL-12, TNF-α, and IFN-γ, and this expression was paralleled by containment and mitigation of the infection. The cytokine response may be part of a local barrier function of the skin, important to host protection against tularemia.